Magnetostructural Transformation and Magnetocaloric Properties of (Ni37.5Co12.5Mn35Ti15)100−xBx (x = 0.0 and 0.4) Melt-Spun Ribbons - Mauricio López-Cruz; Rastislav Varga; José Luis Sánchez Llamazares (Metals, 2024)
The effect of B-doping on the martensitic transformation (MT), microstructure, room temperature (RT) crystal structure, and magnetocaloric properties of a typical all-d-metal Ni37.5Co12.5Mn35Ti15 quaternary alloy was studied by synthesizing melt-spun ribbon samples of nominal composition (Ni37.5Co12.5Mn35Ti15)100−xBx with x = 0.0 and 0.4. For B-free samples, SEM images show a grain-oriented microstructure formed by the columnar in shape-elongated grains with their major axis oriented along the thermal gradient during solidification. By contrast, the B-doped samples show smaller grains whose orientation tends to be perpendicular to the contact surface with the copper wheel. For all samples, austenite (AST) and martensite (MST) phases exhibited a cubic B2-type and 5M monoclinic crystal structure, respectively. The martensitic transition temperature (TM) and the Curie temperature of the austenite phase (TCA) were reduced from 295 K to 253 K and 333 K to 276 K, respectively, with the addition of B. The effect of thermal annealing for different times (from 30 min to 4 h) at 1073 K was studied. Thermal annealing increases the martensitic transformation temperature, whereas TCA remains unchanged. The maximum magnetic field-induced entropy changes |ΔST|max for B-doped samples were around 4.5 J kg−1 K−1 and 4.7 J kg−1 K−1 for as-solidified and annealed samples (1073 K–4 h), respectively, compared to that found for the undoped samples (i.e., ΔST = 16 J kg−1 K−1). However, the entropy reduction is accompanied by an increase in the full width at half-maximum of the ΔST(T) curve.